The Application of Marketing Mix in Increasing Sales at the Integrated Training and Skills Development Center (PLKT) BNKP Gunungsitoli - Waruwu, Walina; Harefa, Idarni; Mendrofa, Yupiter; Zebua, Emanuel (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This research aims to analyze the application of the marketing mix in increasing sales at the Integrated Training and Skills Development Center (PLKT) BNKP Gunungsitoli. The marketing mix includes product, price, place, promotion, people, process, and physical evidence. The study uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that the implementation of the marketing mix has significantly contributed to increased public interest and purchase decisions at PLKT BNKP. Product variation and quality were found to attract customer attention, while competitive pricing strategies enhanced accessibility. Promotional efforts, especially through social media and community involvement, helped build brand awareness. Additionally, the role of skilled human resources, efficient service processes, and the physical environment of the institution also influenced consumer trust and loyalty. The findings suggest that a consistent and well-integrated marketing strategy is essential for sustaining business growth in training and skills development institutions.